Strategies for strengthening attitudes of religious tolerance in students at junior high school - Hamdani, Fakih; Nurchamidah; Safingah, Kuni (TAWAZUN: Jurnal Pendidikan Islam, 2025)
This study is motivated by the importance of strengthening tolerance in junior secondary schools as part of efforts to cultivate a generation capable of living harmoniously in a plural society. The research aims to analyze the strategies employed to strengthen tolerance at SMP Negeri 2 Somagede and to identify the supporting and inhibiting factors. A qualitative approach with a case study design was applied. Data were collected through in-depth interviews, participatory observations, simple questionnaires, and document analysis, and were examined using Miles and Huberman’s interactive analysis model. The findings reveal that tolerance is reinforced through four main strategies: institutional policies emphasizing anti-discrimination principles, integration of tolerance values into teaching subjects such as Civic Education, Islamic Education, and Bahasa Indonesia, inclusive extracurricular activities including Scouts, student councils, and cultural arts, as well as religious accommodations provided for minority students. Supporting factors include inclusive leadership from the principal, teachers’ commitment, and acceptance from the majority group, while inhibiting factors are related to limited facilities. The study concludes that tolerance building in schools requires a synergy of policy, pedagogy, extracurricular programs, and community support, ensuring that tolerance becomes a lived practice in students’ daily life. Abstrak Penelitian ini dilatarbelakangi oleh pentingnya penguatan sikap toleransi di sekolah menengah pertama sebagai upaya membentuk generasi yang mampu hidup harmonis dalam masyarakat yang plural. Tujuan penelitian adalah menganalisis strategi penguatan toleransi di SMP Negeri 2 Somagede serta mengidentifikasi faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, angket sederhana, serta telaah dokumen, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa strategi penguatan toleransi dilaksanakan melalui empat jalur utama, yaitu kebijakan kelembagaan yang menekankan prinsip anti diskriminasi, integrasi nilai toleransi dalam pembelajaran PPKn, PAI, dan Bahasa Indonesia, kegiatan ekstrakurikuler yang inklusif seperti Pramuka, OSIS, dan seni budaya, serta akomodasi kebutuhan keagamaan siswa minoritas. Faktor pendukung mencakup kepemimpinan kepala sekolah yang inklusif, sikap guru, serta penerimaan sosial siswa mayoritas, sedangkan faktor penghambat meliputi keterbatasan fasilitas. Simpulan penelitian ini menegaskan bahwa penguatan toleransi di sekolah menuntut keterpaduan antara kebijakan, pembelajaran, aktivitas kesiswaan, dan dukungan komunitas sehingga toleransi menjadi praktik nyata dalam kehidupan sehari-hari siswa.